Adult obstructive sleep apnoea and the larynx. Issue 6 (December 2015) - Novakovic, Daniel; MacKay, Stuart
Abstract : Purpose of review: The review examines current evidence and thinking regarding the relationship between the larynx and obstructive sleep apnoea (OSA) in adults. Recent findings: Drug-induced sleep endoscopy has an emerging role in the identification of laryngeal obstruction associated with sleep apnoea and may be adjunctive to awake dynamic assessment in specific cases. Nocturnal stridor and OSA is a common and treatable finding in patients with multiple system atrophy. Acromegaly can cause OSA by obstruction at the laryngeal level via supraglottic soft tissue hypertrophy or decreased vocal fold mobility. Emerging evidence suggests a relationship between OSA, laryngopharyngeal reflux, and laryngeal sensory dysfunction including chronic cough. The mechanisms remain unclear and warrant further investigation. Summary: The larynx plays an important role in assessment and treatment of adult sleep apnoea. Laryngeal afferent sensory pathways play a critical role in reflexes controlling airway patency during sleep. Airway obstruction at the laryngeal level should be considered and assessed especially in OSA patients nonresponsive to standard therapies. Isolated laryngeal airway obstruction is rare but identification of specific conditions is important as they are amenable to appropriate treatments. OSA can also affect normal laryngeal function. People with OSA exhibit higher levels of laryngeal inflammation, laryngopharyngeal reflux, and chronic cough. Treatment with continuous positive airway pressure has a potential role in improving laryngeal symptomatology in these cases.